Assessment of Fire Risk and Forest Fires in Rural Areas Using Long Range Technology - Smys, S.; Raj, Jennifer S. (Journal of Electronics and Informatics, 2020)
The occurrences of forest fires is not only a progressing concern in the lives of the people but also in the deterioration of the environment. Since the emergence of the internet of things, new methodologies are being continuously devised to have an early knowledge about the occurrence of the forest fires. The identifying the areas with the fire risks and the intimating it to the public would minimize the death rate caused due to these types of fire accidents. So the paper utilizes the cost- effective network that is centered on long range technology to automatically assess the degree of fire risky and forest fire rural areas and transmit to the website for public vision using the things network server. The proposed method includes many long range nodes and the sensing element to measure the atmospheric changes and the CO2 level in the environment. The long range based sensor network used in the detection of the fire risky and the forest fire areas is evaluated using the network simulator-2 and was found to provide an enhanced service quality by providing a better coverage, battery life, latency, cost and as well as efficiency.
Keywords: Fire Monitoring; Fire Risky Areas; Long Range Technology; Sensor Networks; Things Network